Analisis Pengaruh Stock Split Terhadap Harga Saham, Volume Perdagangan Dan Return Saham Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Pascalina V. S. Sesa; Hastutie N. Andriati; Debora Tamba (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The increase in the stock price that is too high causes the demand for the purchase of the stock to decrease, and affects the liquidity of the stock. To avoid these conditions, companies can take stock split actions which are expected to increase stock liquidity. This study aims to determine the effect of stock splits on stock prices, stock trading volume and stock returns in companies listed on the Indonesia Stock Exchange. The population of this study is companies listed on the Indonesia Stock Exchange. The sample used in this study were 45 companies that carried out a stock split for the 2015-2019 period with a sampling technique using purposive sampling. The window period is 5 days before and 5 days after the stock split. This study uses the SPSS 21 test tool. The data analysis used is a non-parametric paired sample difference test, namely the Wilcoxon test because the data is not normally distributed with 5%. The results showed that there were differences in stock prices, trading volume and stock returns before and after the stock split with a significance value of 0.000, 0.000, and 0.007. Thus, stock splits affect stock prices, trading volume and stock returns. Keywords : Stock price, Stock Split, Stock returns, Trading Volume